2009
DOI: 10.1158/1078-0432.ccr-08-1946
|View full text |Cite
|
Sign up to set email alerts
|

Phase I Study of YM155, a Novel Survivin Suppressant, in Patients with Advanced Solid Tumors

Abstract: Purpose: YM155, a novel molecular targeted agent, suppresses survivin, a member of the inhibitor of apoptosis protein family that is overexpressed in many tumor types. The aim of this study was to determine the maximum tolerated dose (MTD) and to assess the safety, pharmacokinetics, and antitumor activity of YM155 in patients with advanced refractory solid tumors. Experimental Design: Patients with advanced refractory solid tumors were treated with escalating doses of YM155 administered by continuous i.v. infu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
125
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 158 publications
(130 citation statements)
references
References 20 publications
5
125
0
Order By: Relevance
“…Several clinical studies of YM155 revealed that it was very well tolerated, but likely would be best utilized in combination chemotherapy due to its limited single-agent efficacy (44)(45)(46)(47)(48). Multiple combination studies with YM155 were conducted with paclitaxel or docetaxel regimens based on the rationale that YM155 may be able to overcome taxane-mediated upregulation of survivin expression, which promotes drug resistance (44,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Several clinical studies of YM155 revealed that it was very well tolerated, but likely would be best utilized in combination chemotherapy due to its limited single-agent efficacy (44)(45)(46)(47)(48). Multiple combination studies with YM155 were conducted with paclitaxel or docetaxel regimens based on the rationale that YM155 may be able to overcome taxane-mediated upregulation of survivin expression, which promotes drug resistance (44,(48)(49)(50).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that YM155 significantly enhanced the antitumor effect of erlotinib in EGFR mutation-positive NSCLC cells with PTEN loss both in vitro and in vivo. YM155, a small-molecule inhibitor of the expression of the antiapoptotic protein survivin, is currently in clinical development as the first survivin suppressant (18,19,(34)(35)(36). This drug was found to exhibit a favorable safety tolerability profile and moderate single-agent activity in a recent phase II trial with patients with advanced, refractory NSCLC (37).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, the most intensively investigated survivin antagonist is the small imidazolium-based compound YM155 (Sepantronium bromide). This small molecule survivin inhibitor demonstrated impressive anticancer activity in several preclinical studies using cancer cell lines originating from various types of cancer, including GC cells (30,(48)(49)(50) and was well tolerated in phase I studies (51,52). Concerning the potential efficacy of anti-XIAP treatment strategies in GC initial promising results have been published.…”
Section: Svv (Cyt)-center Svv (Cyt)-invasion ----------------------mentioning
confidence: 99%